OVERVIEW OF SOCIAL INTERACTION OF ASD CHILDREN IN THE INCLUSIVE SCHOOL OF SD MUHAMMADIYAH 2 TULANGAN - Kurung , Amalia Dinda Lestari; Mariyati, Lely Ika (Journal of Social Science, 2024)
The purpose of this study was to determine the description of the form of social interaction and the factors that influence the social interaction of ASD children at SD Muhammadiyah 2 Tulangan. This research uses a qualitative method with a case study approach. The subjects of this study amounted to 2 people selected by purposive sampling, namely children with autistic/ASD disorders aged 9 to 12 years. Data collection was carried out using observation and interviews with significant others, namely shadow teachers, parents and peers. The results of this study indicate that both subjects can bring up images of associative and dissociative social interactions but there are differences between the two subjects caused by factors of imitation of other people's behavior, age factors, parenting patterns in establishing cooperation with children, peer interaction and therapy factors